2010
DOI: 10.3109/02841850903292743
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging signal reduction may precede volume loss in the pituitary gland of transfusion-dependent beta-thalassemic patients

Abstract: Pituitary MRI findings such as signal intensity reduction and decrease in volume can be useful markers in estimating pituitary dysfunction in beta-thalassemic patients. Compared to healthy controls, lower values of pituitary-to-fat SIRs in thalassemic patients experiencing normal puberty, without marked decrease in volume, indicate that signal reduction may precede volume loss and could be expected first on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Our results are consistent with their findings. Most recently, Hekmatnia et al [51] estimated the pituitary gland volume 479 ± 127.74 mm 3 using mathematical formulas. In our study, however, we found that the pituitary gland volume was 432.82 ± 147.38 mm 3 using elliptic formula.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with their findings. Most recently, Hekmatnia et al [51] estimated the pituitary gland volume 479 ± 127.74 mm 3 using mathematical formulas. In our study, however, we found that the pituitary gland volume was 432.82 ± 147.38 mm 3 using elliptic formula.…”
Section: Discussionmentioning
confidence: 99%
“…[161718192021] In addition, protein kinase C has been shown to be regulated by iron with possible deleterious effect of excess iron on its function. [212223] Both mechanisms appear to be affected by iron overload and can explain the defective TSH secretion in response to low FT4 in thalassemic patients. The deposition of iron in the pituitary gland and its deleterious effects on pituitary size and functions has been reported in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…21 Therefore, it is advantageous to reverse R2 overload before volume loss and clinical symptoms occur. 6,12 There is currently little literature reporting normative data for R2. 7,22 Additionally, we aimed to supplement current pituitary volume literature [14][15][16] by deriving sex-appropriate z-score calculations for pediatric and adult controls.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11 There has also been evidence that increased R2 precedes pituitary volume loss and hypogonadism. 12 We have demonstrated that R2 deposition can be seen in children as young as 4 years of age, with volume loss beginning in the second decade of life. 13 These findings suggest that proper MR imaging screening may identify iron-mediated HH before it is clinically observable in at-risk patients.…”
mentioning
confidence: 99%